1981
DOI: 10.1073/pnas.78.10.6116
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of displacement-loop strands in human and mouse mitochondrial DNA is arrested near specific template sequences.

Abstract: Animal mitochondrial DNA (mtDNA) maintains a displacement loop (D loop) at the heavy strand origin of replication. These D loops represent sharply limited synthesis ofheavy strands and provide a unique opportunity to examine the termination of DNA synthesis. Direct sizing at the nucleotide level indicates that the 3' ends of D-loop strands of human and mouse mtDNA are discrete and map within three to five nucleotides on the complementary template strand. In the case of human mtDNA, there is a single trinucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
150
0
3

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(164 citation statements)
references
References 15 publications
11
150
0
3
Order By: Relevance
“…Saunders and Edwards (2000) studied dynamics and phylogenetic implications of mtDNA CR sequences in the New World Jays and found a slow rate of evolution in the CR. They suggested that their data indicated a higher Studies have showed that CR contains sequences related to termination of H-strand replication, the origin of H-strand, and promoters of transcription to both L-and H-strand (Doda et al, 1981;Randi and Lucchini, 1998;Saccone et al, 1991;Sbisà et al, 1997;Southern et al, 1988). This indicates that the CR has evolutionary constraints.…”
Section: Dynamics Of the Evolutionary Rate Of Crmentioning
confidence: 98%
“…Saunders and Edwards (2000) studied dynamics and phylogenetic implications of mtDNA CR sequences in the New World Jays and found a slow rate of evolution in the CR. They suggested that their data indicated a higher Studies have showed that CR contains sequences related to termination of H-strand replication, the origin of H-strand, and promoters of transcription to both L-and H-strand (Doda et al, 1981;Randi and Lucchini, 1998;Saccone et al, 1991;Sbisà et al, 1997;Southern et al, 1988). This indicates that the CR has evolutionary constraints.…”
Section: Dynamics Of the Evolutionary Rate Of Crmentioning
confidence: 98%
“…The relevance of DSBs in deletion generation was demonstrated in a mouse model, where strand breaks were induced by expression of a mitochondrially targeted endonuclease (71). In this model system, many of the deletions had a breakpoint within the D-loop region of the mitochondrial genome, close to the replication-relevant termination associated sequence (72).…”
Section: Genetic Mechanisms Explaining Disease Progressionmentioning
confidence: 99%
“…This sequence is read on the complementary strand (Clary and Wolstenholme 1987), and with a few nucleotide changes, it is the one highlighted in the pink box of Figure 1 and the grey box in Figure 2a. Interestingly, within this structure, there is an almost exact match of a stop signal described in humans and mice by Doda et al (1981) which has the motif 5′-ACAT TAAAYYAAT-3′ and is present on A. mellifera c o m p l e m e n t a r y s t r a n d a s 5 ′ -AT AT TA AAATAAT-3′ (bold letters denote mutated nucleotides, see sequence underlined in CB1 of Figure 1 and also Figure 2a). This sequence, highlighted in pink in Figure 2, is conserved in all individuals analyzed but never forms a single stem and loop structure contrary to the Apis model proposed by Zhang et al (1995, see their Figure 4c) unless at a high energetic cost.…”
Section: A G a A A T A T C A A T A A A T A A A G C T T C T A A C T T Tmentioning
confidence: 99%